MATHEMATICAL TASKS AS A MEANS OF IMPROVING THE ECOLOGICAL CULTURE OF THE FUTURE TEACHERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
With the development of civilization, the environment takes an increasing place in our lives. Analysis of the current state of environmental education of students in the University allows to make a conclusion about the need for a comprehensive approach to the problems of formation of ecological culture of future teachers. One of the directions is the integration of mathematics and ecology. Environmental knowledge can be generated when the study of mathematics through the solution of tasks with environmental content. This article presents mathematical tasks with environmental contents of the different sections of mathematics. Jobs can be used in the process of teaching mathematics students of a direction "Pedagogical education".